PENGARUH KUALITAS PELAYANAN DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN PADA APLIKASI SHOPEE DI KALANGAN MASYARAKAT TAMANTIRTO, BANTUL, YOGYAKARTA - Sutrisno, Erwan; Khairul Azmi Hafrin (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2025)
This study aims to analyze the influence of service quality and promotion, both partially and simultaneously, on purchase decisions among Shopee application users in the Tamantirto area, Bantul, Yogyakarta. A quantitative approach was employed using purposive sampling techniques, involving 100 respondents. Data were collected through online questionnaires. The data obtained were analyzed using multiple linear regression, partial test (t-test), simultaneous test (F-test), as well as correlation and determination coefficient calculations. The analysis results show that both service quality and promotion have a significant influence on purchase decisions, both individually and collectively. The correlation coefficient (R) reached 0.828, while the Adjusted R Square value was 0.680, indicating that both independent variables contribute strongly to the dependent variable.